Vital Pulp Therapy—Current Progress of Dental Pulp Regeneration and Revascularization - Weibo Zhang; Pamela C. Yelick (International Journal of Dentistry)
Pulp vitality is extremely important for the tooth viability, since it provides nutrition and acts as biosensor to detect pathogenic stimuli. In the dental clinic, most dental pulp infections are irreversible due to its anatomical position and organization. It is difficult for the body to eliminate the infection, which subsequently persists and worsens. The widely used strategy currently in the clinic is to partly or fully remove the contaminated pulp tissue, and fill and seal the void space with synthetic material. Over time, the pulpless tooth, now lacking proper blood supply and nervous system, becomes more vulnerable to injury. Recently, potential for successful pulp regeneration and revascularization therapies is increasing due to accumulated knowledge of stem cells, especially dental pulp stem cells. This paper will review current progress and feasible strategies for dental pulp regeneration and revascularization.